Reflexive constructions in Bangime - (:unkn) unknown (My University, 2023)
Bangime, a language isolate spoken in Central Eastern Mali, has two ways to express coreference between clause participants. One strategy is through coordinated markers from one of the language’s pronominal series. These markers can be considered to be the language’s reflexive pronouns, though it is of typological interest to note that, in object position, an anaphoric pronoun of this series can be coreferential with the main clause’s subject. Furthermore, Bangime displays the unusual property of aligning second persons singular and plural to the exclusion of all other persons. This chapter also discusses an additional coreference strategy, namely that of a possessed form of the noun ‘head’, an areally robust feature of West Africa.
Keywords: African Research